Making it : manufacturing techniques for product design - Lefteri, Chris (London : Laurence King Publishers, 2012)
"Making It uses contemporary design as a vehicle to describe production processes. It lists their pros and cons, suitable production volumes, costs involved, speed of production, relevant materials, and typical applications. The new edition .. also evaluates each process in terms of sustainablility and its effects upon the environment"--Back cover
1. Cut from solid -- 2. Sheet -- 3. Continuous -- 4. Thin & hollow -- 5. Into solid -- 6. Complex -- 7. Advanced -- 8. Finishing techniques
Includes index
Previous ed.: 2007
Keywords: Industrial design -- Handbooks, manuals, etc; Manufacturing processes -- Handbooks, manuals, etc